Dawr māddat al-jidāl al-ʿArabī fī tarqiyat mahārat al-kalām (dirāsah waṣfiyyah li-ṭullāb al-faṣl al-rābiʿ bi-qism taʿlīm al-lughah al-ʿArabiyyah fī Jāmiʿah Hasyim Asy'ari Tebuireng, Jombang, Jāwī al-Sharqiyyah) - Muhammad Abdullah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
Learning arabic speaking skills is taught in MI until lectures. But in general, students are still not able to express Arabic in the learning process. They still have trouble communicating ideas, thoughts, questions, etc. in Arabic. Therefore, the situation of students who previously did not understand Arabic caused students difficulty in expressing Arabic. This is also experienced by some students of the fourth semester of Arabic language education program Hasyim Asy'ari University who are the subject of research. The purpose of this research is to find out the speaking skills of university students hasyim asyari class 4. To know the application of arabic debate methods in arabic language learning to improve the speaking skills of university students hasyim asyari class 4. To know the role of the application of arabic debate methods in arabic language learning to improve the speaking skills of university students hasyim asyari class 4. This study uses qualitative research sourced from observations, interviews and documents. (1) For the development of speaking skills of students in class 4 pba unhasy still arguably not all mastered and have not developed because of the different differences in individual students themselves. (2) that jidal courses are one of the courses that rely on two aspects, namely dexterity in thinking, which students are trained to be able to speak and must also be sharp in thinking. (3) the role of jidal courses in the improvement of maharah kalam is actually very good but because learning becomes online and causes not conducive learning situations so that students do not speak directly.